Wave File Compression Analysis and Implementation using The Huffman Method - Siagian, Edward Robinson (Ilmu Bersama Center, 2022)
One of the sound file formats that are widely used in the Windows operating system is the Wave format (*. WAV). This format is widely used for gaming and multimedia purposes. Wave is actually a raw format where the voice signal is directly recorded and quantized into digital data. The basic format of this file by default does not support compression and is known as PCM (Pulse Code Modulation). If you record a CD Audio quality song using a sampling rate of 44.1 kHz, 16 bits per sample, 2 channels (stereo), then the total media required to store this audio data per second is 176,400 bytes, so for a duration of 1 minute it takes 10,584 MB. If the average duration of one song is 5 minutes, it takes more than 50 MB of space to store the audio data of the song. This is of course very wasteful of storage media such as hard disks even though there are currently large hard disk capacities available.